A self-controlled comparative study of mini punch graft versus suction blister epidermal graft in the treatment of stable vitiligo. (18th August 2021) - Ding, Xiaolan; Zhao, Mingfu; Li, Man; Du, Juan
Abstract: Background: Mini punch graft (MPG) and suction blister epidermal graft (SBEG) are both effective for stable vitiligo, but there is a lack of self-controlled comparison between these two procedures. Objective: To compare the efficacy and safety of MPG and SBEG in stable vitiligo. Materials and methods: Twenty-three patients were enrolled in this study. A single white patch from each patient was divided into two halves, one half was treated by MPG, while the other half was treated by SBEG (blister or dermabrasion for recipient site), followed by narrow-band UVB irradiation twice a week for 3 months. The repigmentation rate, relative melanin index (RMI), and relative erythema index (REI) were measured at different time points. Results: The repigmentation rate of grafts was 98.7% (312/316) in MPG, 98% (49/50) in SBEG (blister for recipient site) and 99.3% (272/274) in SBEG (dermabrasion for recipient site). The RMI and REI at different time points had no statistical difference between MPG and SBEG. Cobblestone appearance was the predominant complication in SBEG. For MPG, superficial scar occurred in two cases in recipient sites and no obvious side effects in donor sites. Conclusions: MPG is much easier, faster with less side effects in donor site.